2010
DOI: 10.1097/bot.0b013e31819c0ccb
|View full text |Cite
|
Sign up to set email alerts
|

Complications Associated With Negative Pressure Reaming for Harvesting Autologous Bone Graft: A Case Series

Abstract: A technical benefit of the reamer-irrigator-aspirator (RIA) system (Synthes, Paoli, PA) is the ability to harvest large volumes (40-90 cm3) of autogenous bone graft. Early evaluations of this technique have reported few problems, all of which were attributed to technical error. This case series reviews 6 RIA-associated complications including 4 fractures and their contributing risk factors. Cases were collected from 4 independent orthopaedic centers, and all patients underwent RIA bone graft harvesting in a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 29 publications
0
25
0
2
Order By: Relevance
“…The case series of complications reported by Lowe et al is a concern; however, it is unclear as to the incidence of these events from this report [25]. The other evidence suggests that the RIA is relatively safe, with a relatively low rate of complications (three of 87 cases) [5,[7][8][9].…”
Section: Safety Of the Riamentioning
confidence: 44%
See 1 more Smart Citation
“…The case series of complications reported by Lowe et al is a concern; however, it is unclear as to the incidence of these events from this report [25]. The other evidence suggests that the RIA is relatively safe, with a relatively low rate of complications (three of 87 cases) [5,[7][8][9].…”
Section: Safety Of the Riamentioning
confidence: 44%
“…A more recent case series (six patients) of RIA related complications reported three diaphyseal fractures, one trochanteric fracture and two cortical breeches. These were all successfully treated with intra-medullary nail (four of six cases) and cephallomedullary nail (one of six cases) fixation, and in one case the cortical breech was deemed sufficiently small to manage non-operatively [25]. Belthur et al found a reduction in postoperative pain when compared with conventional iliac crest bone graft (ICBG) harvest and overall the RIA appears well tolerated [5].…”
Section: Safety Of the Ria Reamermentioning
confidence: 99%
“…Although it is advantageous compared to standard iliac crest graft harvesting in terms of graft volume, donor side morbidity and possibly quality of graft [1,3,7], it is not without complications. Previous studies have highlighted the possibility of fractures and cortical breaching [1,2,[4][5][6]. Although the possibility of significant blood loss has also been mentioned in the majority …”
Section: Discussionmentioning
confidence: 99%
“…Its indications have expanded since then, and it is now used for intramedullary debridement for the treatment of osteomyelitis and for bone graft harvesting [1,2]. of these studies [2,[4][5][6]8], there are not many reported cases with massive blood loss. Quintero et al6reported on 20 cases; one of them developed intraoperative hypovolemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation